Analysis of insulin injection pen use by people with diabetes mellitus: an integrative review (Research, Society and Development, 2022)
Injector pens represent a major advance in the forms of insulin delivery, optimizing the treatment of DM. The vast majority of patients prefer injection pens as a means of delivering insulin because of their greater ease of use, confidence in dosing accuracy, and less injection pain. The main objective of this study is to analyze the preference regarding the use of injection pens by patients with DM. This is an integrative review, whose data were collected from February 27 to March 04, 2022 and the PUBMED, SciELO and LILACS databases were used. The following search strategies were carried out: “caneta injetora” AND “diabetes”; “injection pen” AND “diabetes”; “caneta injetora” AND “insulina” and “injection pen” AND “insulin”. Patients with DM choose injectable insulin devices based on confidence in delivering the correct dose, ease of selecting the correct dose, overall ease of use of the injection device, frequency of injections, and ease of transporting the device when injecting is required. out of home. Devices that are easy to handle and that induce a feeling of confidence about accurate and reliable injection have a higher acceptance rate. It is concluded that the existence of different models of injector pens allows the user to be able to choose the device that best suits him, taking into account his physical, financial and social characteristics.